New forms and expressions of conflict at work (Basingstoke, 2013)
"A survey and analysis of the new forms and expressions of conflict at work under capitalism. This collection uses theoretical and empirical approaches to demonstrate that there is an underlying historical continuity to current and new forms and expressions of conflict at work and that there is also a path dependency by country and culture. Although the strike is in decline in many countries, it is not so in all and different means of expressing and resolving collective grievances are used but not always as substitutes to the weapon of strike."